Population Pharmacokinetic Assessment and Pharmacodynamic Implications of Pediatric Cefepime Dosing for Susceptible-Dose-Dependent Organisms - Shoji, Kensuke (Antimicrob Agents Chemother, 2016)
The Clinical and Laboratory Standards Institute (CLSI) revised cefepime (CFP) breakpoints for Enterobacteriaceae in 2014, and MICs of 4 and 8 μg/ml were reclassified as susceptible-dose dependent (SDD). Pediatric dosing to provide therapeutic concentrations against SDD organisms has not been defined. CFP pharmacokinetics (PK) data from published pediatric studies were analyzed. Population PK parameters were determined using NONMEM, and Monte Carlo simulation was performed to determine an appropriate CFP dosage regimen for SDD organisms in children. A total of 664 CFP plasma concentrations from 91 neonates, infants, and children were included in this analysis. The median patient age was 1.0 month (interquartile range [IQR], 0.2 to 11.2 months). Serum creatinine (SCR) and postmenstrual age (PMA) were covariates in the final PK model. Simulations indicated that CFP dosing at 50 mg/kg every 8 h (q8h) (as 0.5-h intravenous [i.v.] infusions) will maintain free-CFP concentrations in serum of >4 and 8 μg/ml for >60% of the dose interval in 87.1% and 68.6% of pediatric patients (age, ≥30 days), respectively, and extending the i.v. infusion duration to 3 h results in 92.3% of patients with free-CFP levels above 8 μg/ml for >60% of the dose interval. CFP clearance (CL) is significantly correlated with PMA and SCR. A dose of 50 mg/kg of CFP every 8 to 12 h does not achieve adequate serum exposure for older children with serious infections caused by Gram-negative bacilli with a MIC of 8 μg/ml. Prolonged i.v. infusions may be useful for this population.